2008
DOI: 10.1038/sc.2008.137
|View full text |Cite
|
Sign up to set email alerts
|

Management of neurogenic bowel dysfunction in the community after spinal cord injury: a postal survey in the United Kingdom

Abstract: Study design: Postal survey. Objectives: To describe bowel management in community-dwelling spinal cord-injured (SCI) individuals and to explore associations between age, injury, dependency, problems, interventions and satisfaction. Setting: Outpatients of a single SCI unit, in the United Kingdom. Methods: Postal questionnaire to all outpatients with SCI for at least 1 year, of any level or density, aged 18 years or more. Results: Response rate was 48.6% (n ¼ 1334). Median age was 52 years, median duration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
129
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(141 citation statements)
references
References 18 publications
(21 reference statements)
5
129
1
4
Order By: Relevance
“…The results of our study are compatible with another study that reported significant associations between AD and manual evacuation. 13 Manual removal of stool is the only method used by many patients with SCI especially those with complete lesion, 8 because of the lack of non-invasive and efficient bowel management methods for defecation. Furthermore, it has been reported that manual removal of stool is associated with low risk of unplanned bowel evacuation and short duration of evacuation time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results of our study are compatible with another study that reported significant associations between AD and manual evacuation. 13 Manual removal of stool is the only method used by many patients with SCI especially those with complete lesion, 8 because of the lack of non-invasive and efficient bowel management methods for defecation. Furthermore, it has been reported that manual removal of stool is associated with low risk of unplanned bowel evacuation and short duration of evacuation time.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Recently, Coggrave et al used postal questionnaire to investigate the management of neurogenic bowel dysfunction in the community after SCI. 13 They received responses from 1334 persons with SCI (response rate: 48.6%) and reported that AD was a frequent complication of bowel care in 9.5% of those with injuries above T7. 13 Furthermore, significant associations were noted between AD and certain interventions such as manual evacuation in persons with cervical SCI, laxatives (stimulant) and chemical rectal stimulants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…When BM is ineffective, bowel dysfunction may dominate day-to-day life, severely curtailing community reintegration and reducing quality of life. [3][4][5] Neurogenic bowel dysfunction can result in considerable morbidity, such as autonomic dysreflexia, impaction, hemorrhoids, abdominal pain, rectal bleeding, rectal prolapse, anal fissure, bloating, nausea, constipation and prolonged evacuation. 1,3,4,6,7 Bowel management programs are based on regular routine, dietary manipulation, laxatives, digital and pharmacological rectal stimulation, manual evacuation of stool and assistive interventions such as abdominal massage.…”
Section: Introductionmentioning
confidence: 99%